Building, codifying, and applying the analytical thinking scale for handball Premier League players - AbdelWahab, H. S. (Zien Journal of Social Sciences and Humanities, 2023)
The research included four chapters, as the first chapter contained an introduction to the research and its importance,the researcher touched on the importance of analytical thinking and the need to study it in the sports aspect and in the game of handball,as for the problem of the research, it lies in the absence of a scale that measures analytical thinking in the sports side and among handball players. The objectives of the research were building and codifying analytical thinking among handball players for the season (2022-2023) and identifying the level of analytical thinking among handball players in Iraq for the season ( 2022-2023). As for the areas of research, it included the human field, which was represented by the players of handball clubs in Iraq for the sports season (2022-2023), and the temporal field was determined for the period from (6/9/2018) until (7/30/2018), while the spatial field was halls And sports club stadiums in Iraq, and the researcher used the descriptive approach in the survey method, and the research sample consisted of (145) players from Iraqi clubs, and the researcher built and standardized the analytical thinking scale and used to extract the statistical results, the statistical bag (SPSS), and the researcher was able to build and standardize the analytical thinking scale with ( 56) a paragraph divided into four axes, so the researcher recommends that coaches use the current scale to periodically detect the level of their players to know the extent of their readiness and preparation in training and competition.